2005
DOI: 10.1128/aem.71.10.6086-6095.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol Mass Spectrometry for Rapid Detection of Individual Airborne Mycobacterium tuberculosis H37Ra Particles

Abstract: Single-particle laser desorption/ionization time-of-flight mass spectrometry, in the form of bioaerosol mass spectrometry (BAMS), was evaluated as a rapid detector for individual airborne, micron-sized, Mycobacterium tuberculosis H37Ra particles, comprised of a single cell or a small number of clumped cells. The BAMS mass spectral signatures for aerosolized M. tuberculosis H37Ra particles were found to be distinct from M. smegmatis, Bacillus atrophaeus, and B. cereus particles, using a distinct biomarker. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 51 publications
1
58
0
Order By: Relevance
“…Nevertheless, by the analysis of fragment ions that are specific to distinct microorganisms, the types of viruses, bacteria, and fungi present in the air can be assessed on an individual-particle basis. The analysis of biomarker ions forms the basis of bioaerosol mass spectrometry (BAMS), a new and highly efficient method for the detection of both spores and vegetative cells of airborne pathogens and bioterrorism agents (Russell et al, 2004Tobias et al, 2005;van Wuijckhuijse et al, 2005;Beddows and Telle, 2005). AMS is now a widely used single-particle method in aerosol science, with unique capabilities for obtaining species-specific data from biological particles.…”
Section: Physical and Chemical Characterization Of Biological Atmosphmentioning
confidence: 99%
“…Nevertheless, by the analysis of fragment ions that are specific to distinct microorganisms, the types of viruses, bacteria, and fungi present in the air can be assessed on an individual-particle basis. The analysis of biomarker ions forms the basis of bioaerosol mass spectrometry (BAMS), a new and highly efficient method for the detection of both spores and vegetative cells of airborne pathogens and bioterrorism agents (Russell et al, 2004Tobias et al, 2005;van Wuijckhuijse et al, 2005;Beddows and Telle, 2005). AMS is now a widely used single-particle method in aerosol science, with unique capabilities for obtaining species-specific data from biological particles.…”
Section: Physical and Chemical Characterization Of Biological Atmosphmentioning
confidence: 99%
“…T he Bioaerosol Mass Spectrometry (BAMS) system was developed for national security and public health applications including the real-time, in situ detection of airborne pathogens [1] and biowarfare agents [2,3]. It has the ability to distinguish Bacillus spores from vegetative cells on a particle by particle basis using ion peaks under m/z 300 [4], and has demonstrated preliminary species level differentiation of individual Bacillus spores using low mass biomarker peaks [5,6].…”
mentioning
confidence: 99%
“…37 Dale et al demonstrated the detection of 2,4,6-trinitrotoluene (TNT) adsorbed on silicon carbide beads using a single-particle quadrupole ion trap mass spectrometer. 38 Time-of-flight SPAMS at Lawrence Livermore National Laboratory (LLNL) in the form of bioaerosol mass spectrometry (BAMS) has been applied to the detection of various species of Bacillus spores, [39][40][41][42][43][44][45] viruses, 39 toxin simulants, 39 fungi, 41 and Mycobacteria, 45 with and without the use of a chemical matrix during ionization. Matrix-free systems are ideal for real-time and on-line detection systems, as no sample preparation and thus very few reagents are needed for the analysis.…”
mentioning
confidence: 99%